The L2 Motivational Self System and International Posture among Simultaneous Multiple Language Learners: A Study of Gender Differences in the Burundi Context - Elvis Nizigama; Arcade Nduwimana; Clément Ndoricimpa (Raja Zulkarnain Education Foundation, 2026)
Gender differences are a consistent finding in research on second or foreign language (L2) learning motivation, yet this important topic has been scarcely investigated in Burundi. Therefore, this study primarily aimed to examine gender differences in L2 motivation, framed by the L2MSS and International Posture frameworks, among Burundi junior high school students learning simultaneously multiple foreign languages (L2 French, L3 English, and L3 Kiswahili). A secondary aim was to assess whether the years of study (school grade level) moderated the link between gender and L2 motivation. The population was 594 junior high school students per class and per gender who completed and submitted the questionnaire. A sample of 210 students (94 boys and 116 girls) from Grades 7–9 across two public schools completed a questionnaire, and the data was statistically analyzed using SPSS-version 22. The overall results for the whole sample indicated no statistically significant gender differences in L2 motivation across all three target languages. However, the examination of the interaction effect revealed significant gender x school grade interactions on four of the five measured constructs (Ideal L2 Self, Ought-to L2 Self, Intended Learning Efforts, and International Posture), with all significant interactions relating only to English, but not for French or Kiswahili. Further analysis demonstrated that the statistically significant effect was confined only to Grade 7, where female learners consistently exhibited higher mean scores than their male peers, a difference that disappeared in grades 8 and 9. These results underscore the importance of including gender as a key variable in future L2 motivation research in Burundi, particularly with younger participants, such as primary school learners.